Selected genetic aspects of male infertility--what animal models tell us - Liska, F (Folia biologica, 2003)
Many advances have been recently made in understanding the genetic control of fertility in model systems. This review concentrates on genetic causes of male factor infertility in mammalian models. More than 150 genes proved to be important for the male fertility in mammals and the list is continuously growing. Most of those genes were discovered using gene targeting in the mouse. Here, several interesting male infertility mutations are described with regard to the pathogenesis of reproduction failure. A detailed table comprising most of the genes causing male infertility is presented as supplementary Table 1, at http://www.img.cas.cz/fb/v49no4_table1.html, including the corresponding references.
Keywords: modely nemocí na zvířatech; mužské pohlavní orgány; Humans; kryptorchismus; Mice; Cryptorchidism; zvířata; Genitalia, Male; Infertility, Male; Disease Models, Animal; Spermatogenesis; mužské pohlaví; meióza; Meiosis; spermatogeneze; myši; mužská infertilita; Animals; lidé; Male